Biomaterial-targeted precision nanoparticle delivery to the injured spinal cord. (15th October 2022) - Ciciriello, Andrew J.; Surnar, Bapurao; Medy, Giovanni D.; Su, Xiaoyu; Dhar, Shanta; Dumont, Courtney M.
Abstract: Drug delivery requires precision in timing, location, and dosage to achieve therapeutic benefits. Challenges in addressing all three of these critical criteria result in poor temporal dexterity, widespread accumulation and off-target effects, and high doses with the potential for toxicity. To address these challenges, we have developed the BiomatErial Accumulating Carriers for On-demand Nanotherapy (BEACON) platform that utilizes an implantable biomaterial to serve as a target for systemically delivered nanoparticles (NPs). With the BEACON system, administered NPs are conjugated with a ligand that has high affinity for a receptor in the implanted biomaterial. To test BEACON, an in vivo spinal cord injury (SCI) model was used as it provides an injury model where the three identified criteria can be tested as it is a dynamic and complicated injury model with no currently approved therapies. Through our work, we have demonstrated temporal dexterity in NP administration by injecting 6 days post-SCI, decreased off-target accumulation with a significant drop in liver accumulation, and retention of our NPs in the target biomaterial. The BEACON system can be applied broadly, beyond the nervous system, to improve systemically delivered NP accumulation at an implanted biomaterial target. Statement of significance: Targeted drug delivery approaches have the potential to improve therapeutic regimens for patients on a case-by-case basis. Improved localization of a therapeutic to site of interest can result in increased efficacy and limit the need for repeat dosing. Unfortunately, targeted strategies can fall short when receptors on cells or tissues are too widespread or change over the course of disease or injury progression. The BEACON system developed herein eliminates the need to target a cell or tissue receptor by targeting an implantable biomaterial with location-controllable accumulation and sustained presentation over time. The targeting paradigm presented by BEACON is widely applicable throughout tissue engineering and regenerative medicine without the need to retool for each new application. Graphical abstract: Image, graphical abstract